Sphingolipid Levels and Signaling via Resveratrol and Antioxidant Actions in Cardiometabolic Risk and Disease - Melania Gaggini; Simona Fenizia; Cristina Vassalle (MDPI AG, 2023)
Resveratrol (RSV) is a phenolic compound with strong antioxidant activity, which is generally associated with the beneficial effects of wine on human health. All resveratrol-mediated benefits exerted on different systems and pathophysiological conditions are possible through resveratrol's interactions with different biological targets, along with its involvement in several key cellular pathways affecting cardiometabolic (CM) health. With regard to its role in oxidative stress, RSV exerts its antioxidant activity not only as a free radical scavenger but also by increasing the activity of antioxidant enzymes and regulating redox genes, nitric oxide bioavailability and mitochondrial function. Moreover, several studies have demonstrated that some RSV effects are mediated by changes in sphingolipids, a class of biolipids involved in a number of cellular functions (e.g., apoptosis, cell proliferation, oxidative stress and inflammation) that have attracted interest as emerging critical determinants of CM risk and disease. Accordingly, this review aimed to discuss the available data regarding the effects of RSV on sphingolipid metabolism and signaling in CM risk and disease, focusing on oxidative stress/inflammatory-related aspects, and the clinical implications of this relationship.